Pengaruh Gaya Kepemimpinan Kepala Sekolah dan Motivasi Terhadap Kedisiplinan Guru Sekolah Dasar (SD) Di Kecamatan Oheo Kabupaten Konawe Utara - Sundi Komba (e-JKPP, 2015)
Problem of this research that is (1) Whether/What Style of Headmaster Leadership have an effect on to Elementary Schoolteacher Discipline in Subdistrict of Oheo of Regency of Konawe North, (2) Whether Motivation have an effect on to to Elementary Schoolteacher Discipline in Subdistrict of Oheo of Regency of Konawe North, (3) How big influence of Style of Headmaster Leadership and Motivate to Elementary Schoolteacher Discipline in Subdistrict of Oheo of Regency of Konawe North.This desain Research is survey eksplanatori with the technique of data collecting of through kuesioner as especial instrument, beside interview the, observation and documentation. this Research responder is altogether Learn Elementary School in Subdistrict of Oheo of Regency of Konawe North, amounting to 48 people, Research done have the character of the census of because entire/all population made by a research responder, so that this sampel research represent the total sampel. While data analysisdone with two way of that is descriptive Analysis qualitative by using presentase with the category. And statistical Analysis by using aid program the SPSS version 17.Result of Research menunjukan that goodness of style of headmaster leadership and also motivate the teacher SD have the influence to discipline learn Elementary Schoolsd in Subdistrict of Oheo of Regency of Konawe North, with the belief storey;levelthat is there is influence of but lowering. By dermikian that progressively goodness of styleof headmaster leadership and progressively goodness motivate the teacher ElementarySchool hence discipline Learn the SD will be good progressively also.